Patterns, predictors and effects of texting intervention on physical activity in CHD - insights from the TEXT ME randomized clinical trial - Thakkar, Jay; Redfern, Julie; Thiagalingam, Aravinda; Chow, Clara K (European journal of preventive cardiology, 2016)
Mobile phone text message interventions are used to support behaviour change including physical activity, but we have less insight into how these interventions work and what factors predict response. To study the effect of TEXT ME (Tobacco EXercise and dieT Messages) text message intervention on physical activity domains, consistency of effects across sub-groups and its additive value in patients that received traditional cardiac rehabilitation programme. This is a secondary analysis of the TEXT ME, a randomized clinical trial of lifestyle-focused text message intervention compared with usual care in patients with coronary heart disease. A quarter of the messages were designed specifically to encourage physical activity. Sedentary time and physical activity were assessed using the Global Physical Activity Questionnaire. At baseline, 85% of the 710 participants reported low physical activity levels. At six months, compared with controls, the intervention arm reported higher recreational physical activity (471 vs. 307 metabolic equivalent-min/week, p = 0.001) and travel physical activity (230 vs. 128 MET-min/week, p = 0.002), similar work-related physical activity and lower sedentary times (494 vs. 587 min, p < 0.001). Male gender, high baseline physical activity, cardiac rehabilitation participation and text message intervention predicted physically active status at six months. Subjects that received both cardiac rehabilitation and text messaging intervention were more likely to achieve target physical activity levels compared with cardiac rehabilitation alone (odds ratio 7.07 vs. 1.80, p < 0.001). The TEXT ME intervention improved recreational and travel physical activity, reduced sedentary times but had no effects on work-related physical activity. It had incremental benefits at achieving target physical activity levels even in patients participating in the traditional cardiac rehabilitation programme.